Family support as a predictor of breastfeeding self-efficacy among postpartum mothers - Tetty Junita Purba; Peny Ariani; Mutiara Dwi Yanti; Putri Ayu Yessy Ariescha; Friska Ernita Sitorus; Jekson Martiar Siahaan (Nursing and Health Sciences Journal (NHSJ), 2026)
While family support is widely acknowledged as a critical determinant of breastfeeding self-efficacy, research on its independent predictive effect remains sparse. This limitation is particularly pronounced among postpartum mothers in Indonesia, where context-specific evidence is currently insufficient. This study aimed to analyze the relationships and effects of family support, educational level, and parity status on postpartum mothers' breastfeeding self-efficacy. A multicenter cross-sectional study was conducted among 180 postpartum mothers recruited from nine primary health centers across urban, semi-urban, and rural areas using purposive sampling. Family support was measured using a Friedman-based questionnaire, and breastfeeding self-efficacy was assessed using the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF). Spearman correlation and multiple linear regression were performed. Family support showed a moderate positive correlation with breastfeeding self-efficacy (rs = 0.559, p < 0.01). In multivariate analysis, family support remained the strongest predictor of breastfeeding self-efficacy (β = 0.509, p < 0.01), followed by parity (β = 0.255, p < 0.001), whereas maternal education was not statistically significant. Family support is the primary determinant of breastfeeding self-efficacy among postpartum mothers. Interventions to improve breastfeeding outcomes should integrate family-centered support strategies, particularly for first-time mothers.